Cardiovascular Risk Profile in Women from Three Different Areas of the Province of Tucumán, Argentina - Holownia, Damián (2023)
Background: The role of the environment on female population health in Tucumán has been little studied. This study aimed to evaluate the cardiovascular risk profile in women from rural, peri-urban and urban areas in the province of Tucumán (Argentina) and to analyse their differences.Methods: An analytical cross-sectional study was conducted in 3 groups of women from Tucumán: rural (n = 125), peri-urban (n = 50) and urban (n = 112).Results: Blood pressure (BP) was lower in the rural group; the urban group showed higher heart rate and smaller neck circumference. Of the studied women, 29.7% were overweight and 42.4% obese, and no significant differences were found in the 3 groups. Increased neck circumference was observed in 62% of women in the rural group, 79% in the peri-urban group and 41% in the urban group (p <0.001). Smoking was more frequent in the urban group. In the urban and peri-urban groups, the proportion of women with higher education level was greater (p <0.001). Education level was positively correlated with heart rate.Conclusion: Regardless of the environment, women from Tucumán are overweight or obese and have other risk factors for cardiovascular disease. This should be considered when planning policies and making decisions in order to improve their prognosis.